Collaborative data management using the Open Science Framework - Magle, C. Tobin, speaker (Colorado State University. Libraries, 2017)
Our access to the web makes collaborating with colleagues at other institutions easier, but it is not without its challenges. In this Data and Donuts, we will cover a tool. After this session you'll be able to how to to store files, easily collaborate with people outside your institution, and link accounts like Google Drive and Dropbox.
Data and donuts
Accessibility features: Transcript.
ZIP file contains: instructional materials and Readme.
Keywords: data management; data storage; data education; Data editing; Data curation